2007
DOI: 10.2341/06-21
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Cycling on Dentin Bond Strengths of Single-step Self-etch Adhesive Systems

Abstract: Some of the bonding systems used in this study have achieved unchanged dentin bond strengths after thermal cycling. Therefore, by choosing appropriate adhesive systems, the simplified clinical procedures offered by single-step self-etch systems can be exploited even after thermal cycle stress. SUMMARYThis study investigated the influence of thermal cycling on the dentin bond strengths of singlestep self-etch adhesive systems. The Absolute, Clearfil Tri-S Bond, G-Bond and One-Up Bond F Plus systems were used. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
0
25
0
3
Order By: Relevance
“…This was a rather unusual result for a bonding system which already exhibited good initial bond strength. In previous studies, at best only a slight increase in bond strength was reported after long-term storage [19][20][21][22] . It has been suggested that loss of minerals from enamel and dentin during in vitro water storage would lead to deterioration of mechanical properties of teeth 31) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a rather unusual result for a bonding system which already exhibited good initial bond strength. In previous studies, at best only a slight increase in bond strength was reported after long-term storage [19][20][21][22] . It has been suggested that loss of minerals from enamel and dentin during in vitro water storage would lead to deterioration of mechanical properties of teeth 31) .…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility of resin components to hydrolysis has been identified as a cause for decrease of bond strength. It has been suggested that the outstanding hydrolytic stability of MDP and its additional chemical interaction with enamel and dentin contributed to the long-term durability of dentin and enamel bonding with SE 17,21) and TS 18,22) . MDP has a special molecular structure that enables chemical interaction with residual hydroxyapatite after etching, and the calcium salts formed thereby also exhibit hydrolytic stabiltiy 21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal cycling induces stress and degradation in interface due to the difference between tooth structures and restorative materials. 21 Mechanical load cycling produces stress in the composite resin, and it is transmitted to the bonding interface. Interfaces less affected by microleakage before the aging test were more susceptible to thermal and load cycling.…”
Section: Discussionmentioning
confidence: 99%
“…17 Bazı çalışmalar, tek aşamalı self-etch sistemlerin termosiklus işleminden etkilenmediğini bildirirken, bazı çalışmalar ise termosiklus işle-minden sonra tek aşamalı self etch sistemlerin bağ-lanma değerlerinin düştüğünü bildirmişlerdir. [116][117][118][119] Adezivin kimyasal yapısına bağlı olarak, 100.000 termosiklus işleminden sonra bile ara yüzde yapısal değişiklikler meydana gelmeyebilir. 120 Lodovici ve arkadaşları, 84 adeziv tabaka kalınlı-ğının, termal ve mekanik uygulamadan sonra bağlan-ma direncini etkileyip etkilemediğini incelemişlerdir.…”
Section: Termosiklus Işlemiunclassified